Innovation In Learning Media Using An Assemblr Edu–Based Augmented Reality Website On Students’ Learning Outcomes - Risqi Dwi Rahmawati; Ratnasari Dyah Utami (FKIP - Universitas Riau, 2026)
Twenty-first-century learning requires students to master critical thinking, creativity, collaboration, and technological literacy to face global challenges. However, learning in elementary schools is still largely dominated by conventional methods, which often result in low student engagement and difficulties in understanding abstract concepts, especially in the IPAS subject. This study aimed to examine the effectiveness of an Assemblr Edu–based Augmented Reality (AR) website in improving students’ learning outcomes. The research employed a quantitative approach using a pretest–posttest control group design involving two sixth-grade classes at SD Muhammadiyah Program Unggulan Colomadu. Data were collected through learning outcome tests and observation sheets that were validated and tested for reliability. Of the 20 test items, 13 were declared valid, and reliability analysis using Cronbach’s Alpha produced a coefficient of 0.936, indicating very high consistency. Statistical tests showed that the use of Assemblr Edu had a significant effect on learning outcomes. The experimental class posttest scores increased from 56.92 to 81.15, while the control class showed a decline. These findings indicate that AR technology provides more concrete, interactive, and meaningful learning experiences for IPAS instruction in elementary schools.